Feasibility of Analytical Thinking Test Instrument: An Analysis of Test Quality and Learner Abilities Using the Rasch Model - Nurbaiti, Urai; Afandi; Tenriawaru, Andi Besse (UNIB Press, 2024)
This study aimed to determine the quality of analytical thinking test instruments and the level of students' abilities through Rasch model analysis. This research used descriptive method with quantitative approach. The sample used amounted to 246 students. The instrument used was an analytical thinking test instrument totaling 9 items in the form of descriptions. Data collection was carried out by testing the test instrument. Data analysis was carried out by Rasch model analysis. The results showed that all items were fit. The level of item difficulty varies consisting of 1 very difficult question, 4 difficult questions, 3 easy questions, and 1 very easy question. Cronbach's alpha value of 0.80 is categorized as good, person reliability value of 0.79 is categorized as sufficient, and item reliability value of 0.98 is categorized as excellent. The level of item difficulty consists of 1 very difficult question, 4 difficult questions, 3 easy questions, and 1 very easy question. Person separation value 1.92 (H = 2.89, rounded to 3) and item separation 6.26 (H = 8.68 rounded to 9). Person measure analysis obtained 114 high ability (46%), 27 medium ability (11%), and 105 low ability (43%). Person fit analysis obtained 178 fits (72%), 2 misfits (1%), and 66 outliers (27%).